Control glucémico y variación de HbA1c de pacientes con diabetes mellitus atendidos en consulta presencial y por teleconsulta en un hospital peruano - López-Huamanrayme, Eddy (2024)
Objective: To assess glycemic control in patients with diabetes mellitus (DM) seen in live consultation or remote consultation, and to identify factors associated with variations in glycated hemoglobin (HbA1c) values. Materials and methods: We did a retrospective cohort study that included patients >18 years old who were seen in live consultation or remote consultation because of DM in Alberto Sabogal-Sologuren National Hospital, during June 2021. Clinical data from electronic clinical records were obtained, including baseline and at 11-month follow-up HbA1c values. We used Poisson regression with robust variance for calculating relative risk (RR) and 95% confidence intervals (CI), for identifying factors associated with ≥0.5 HbA1c variations during follow-up. Results: Four-hundred and sixteen patients were included, their mean age was 62 years, 57.2% were female, and 68.5% had remote consultation. The percentage of patients with HbA1C <7% increased from 21,7 to 27,4% during follow-up, while in those with HbA1C ≥10%, there was a reduction, from 38,2 to 19,1%. Amongst patients with baseline HbA1c ≥7%, having baseline HbA1c ≥10% was associated with ≥0,5% reduction in HbA1c values (adjusted RR: 2,97; 95% CI: 1,61-5,50). The consultation modality (live or remote) was not associated with significant variations in HbA1c levels. Conclusions: One fifth of patients had optimum glycemic control at baseline, and this rate increased during follow-up. Those who had baseline HbA1C ≥10% had greater frequency in HbA1c level reduction, although the consultation modality (live or remote) was not associated with variations in HbA1c levels.